El concepto de informe integrado como innovación en reporting corporativo - Yaismir Adriana Rivera-Arrubla; Ana Zorio-Grima; María A. García Benau (Journal of Innovation & Knowledge (JIK), 2016)
Integrated reporting (IR) is one of the latest innovations regarding sustainability reporting and non-financial information in the world. Although some companies began IR practices in the 2000s (Eccles & Krzus, 2010), IR has only been recognized since 2010 as the best way to get a complete picture of the value of organizations, overcoming the limitations of traditional reports (Eccles & Krzus, 2010; Jensen & Berg, 2012; Abeysekera, 2013).Our research aims to analyze this innovative reporting trend. To do this, we first review some practices in the annual reports published by the pioneering companies in IR, then, we present the antecedents for the current IR framework. Finally we look into the process that the International Integrated Reporting Council has followed to develop the framework, pointing out some milestones for the widespread adoption of integrated reporting.Our findings suggest that reporting practices have been ahead both from theoretical developments and institutional efforts. However, private regulators continue to have a major influence on the theoretical definition of standards that are intended to guide IR and the development of accountability practices to stakeholders.
Keywords: M14; M40; 650; Integrated reporting; Reporting; Financial and non-financial information; First integrated reporting practices; International Integrated Reporting Council pilot programme; The International Integrated Reporting Framework